Indikatoren und Methoden zur Erfassung und Bewertung von Ökosystemleistungen in metropolitanen Räumen - Christian Albert; Reinhard Henke; Janette Iwanowski; Antje Kosan; Dietmar Mehl; Claudia Romelli (Raumforschung und Raumordnung, 2022)
This paper presents a scientifically credible and practically relevant set of indicators and methods to assess and evaluate ecosystem services of relevance for land use and landscape planning. The research questions are (i) to identify suitable ecosystem services, indicators, and methods, and (ii) to assess the proposed indicators regarding the respective data availability and assessment effort. The region of Frankfurt/Rhein-Main (Germany) serves as the case study. The methods include the synthesis of a specifically adapted list of ecosystem services indicators based on relevant prior research and an expert-based and application-oriented evaluation. The proposed list for the region of Frankfurt/Rhein-Main contains 27 ecosystemservices, with one or more associated indicators each. The evaluation reveals that metropolitan regions in Germany usually provide sufficient data to assess almost all ecosystem services. The assessment effort differs, but is generally moderate. The paper concludes with recommendations for practical application in the Frankfurt region and beyond.